Comparing speech acts and complexity of maternal speech to singleton and first-born dizygotic twin infants. Issue 3 (17th February 2023) - Kokkinaki, Theano; Markodimitraki, Maria; Vasdekis, V. G. S.
ABSTRACT: We compared speech acts and complexity of maternal speech to firstborn dizygotic twin and singleton infants. Nine twins and nine singletons were video-recorded at home in spontaneous face-to-face interactions with their mothers, from the 2nd to the 6th month. Continuous micro-analysis revealed that (a) open-ended questions, direct requests, disapprovals and complex utterances predominated in mothers' speech of singletons compared to twins; and (b) mothers of singletons and mothers of twins showed age-related variations in questions and in certain forms of complexity, respectively. In the framework of the theory of innate intersubjectivity, these results show that mothers of twins and mothers of singletons share the ability to adjust sensitively to their young infants' expressive behaviours.